2022
DOI: 10.1007/s00417-022-05931-z
|View full text |Cite
|
Sign up to set email alerts
|

Future perspectives for treating patients with geographic atrophy

Abstract: Purpose Geographic atrophy (GA) is a late-stage form of age-related macular degeneration (AMD) characterized by the expansion of atrophic lesions in the outer retina. There are currently no approved pharmacological treatments to prevent or slow the progression of GA. This review describes the progression and assessment of GA, predictive imaging features, and complement-targeting investigational drugs for GA. Methods A literature search on GA was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Over the past decade, a multitude of clinical trials have been conducted, each contributing significantly to our understanding of geographic atrophy (GA) and its potential therapeutic interventions (Loewenstein & Trivizki, 2023).…”
Section: Completed Trialsmentioning
confidence: 99%
“…Over the past decade, a multitude of clinical trials have been conducted, each contributing significantly to our understanding of geographic atrophy (GA) and its potential therapeutic interventions (Loewenstein & Trivizki, 2023).…”
Section: Completed Trialsmentioning
confidence: 99%
“…Activation of the retinal immune system and accumulation of mononuclear phagocytes in the subretinal space are a common hallmark for AMD pathology in humans ( 5 ). Of note, targeting the innate immune system has been recently proposed as a therapeutic option for the treatment of atrophic AMD ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 Regular intravitreal injections (injections into the eye) are the standard of care for wet AMD and a common mode of delivery in the current pipeline of treatments for GA in clinical trials. Dysregulation of the complement cascade has been implicated in the pathogenesis of GA, and recent positive results from phase 3 clinical trials of two intravitreal complement inhibitors have paved a way for new therapies to treat GA. 4 Findings from the DERBY and OAKS trials of pegcetacoplan have shown that at 24 months, GA lesion growth was reduced by 21% with monthly intravitreal injections…”
Section: Introduction Background and Rationalementioning
confidence: 99%